واقع قياس القيمة العادلة للتثبيتات العينية في الجزائر في ظل المستجدات المحاسبية الدولية - دراسة حالة مجمع صيدال - - سحنون أسامة (جامعة الوادي University of Eloued, 2023)
This study aims to shed light on the most important Updates of the International Accounting Standards Board in the field of measuring the fair value of tangible assets and to determine the reality of its application on the ground in the Algerian economic institution, and in light of the nature of the topic and the objectives that we seek to achieve from this research, the descriptive and analytical approach was used to address the basic aspects of the topic, in addition to conducting an applied study at the level of institution of SAIDAL, through which we obtained information that helped us reach a clearer understanding of the research problem. Among the most important findings of the study is that IFRS 13 was very fair in providing a clear vision about the fair value measurement of tangible assets, and the rules applied by the real estate expert in determining the fair value of the lands and buildings of the SAIDAL compound are largely compatible with the requirements of IFRS 13. Keywords: Fair value ; tangible assets ; IFRS 13 .
The reality of measuring the fair value of tangible assets in Algeria in light of International Accounting Updates - a case study of the SAIDAL compound -
Keywords: القيمة العادلة; التثبيتات العينية; المعيار الدولي لإعداد التقارير المالية IFRS 13; Fair value; tangible assets; IFRS 13